2007
DOI: 10.1007/s10665-007-9199-6
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial capillary–gravity waves due to a fundamental singularity in a system of two semi-infinite fluids

Abstract: The interfacial capillary-gravity waves due to a transient fundamental singularity immersed in a system of two semi-infinite immiscible fluids of different densities are investigated analytically for two-and threedimensional cases. The two-fluid system, which consists of an inviscid fluid overlying a viscous fluid, is assumed to be incompressible and initially quiescent. The two fluids are each homogeneous, and separated by a sharp and stable interface. The Laplace equation is taken as the governing equation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Parau et al [13] analyzed three-dimensional capillary-gravity interfacial flows due to an immersed disturbance that propagates to a constant velocity along the interface between two semi-infinite fluids. Lu and Ng [14] studied interfacial capillary-gravity waves due to a fundamental singularity in a system of two semi-infinite fluids in both two-and three-dimensional cases.…”
mentioning
confidence: 99%
“…Parau et al [13] analyzed three-dimensional capillary-gravity interfacial flows due to an immersed disturbance that propagates to a constant velocity along the interface between two semi-infinite fluids. Lu and Ng [14] studied interfacial capillary-gravity waves due to a fundamental singularity in a system of two semi-infinite fluids in both two-and three-dimensional cases.…”
mentioning
confidence: 99%
“…(22) shall be studied for large t with x/t held fixed. This approximation has been successfully used to study the generalized Cauchy-Poisson problems [29][30][31][32][33].…”
Section: Transient Waves Due To a 2d Instantaneous Stokesletmentioning
confidence: 99%
“…On the other hand, the transient responses to the oscillatory singularity [29,30] do not tend to zero as time goes to infinity, and thus the steady state cannot be attained. These are really singular behaviors from the physical point of view, which is caused by the potential theory in which the energy of wave motion is conservative [31]. One is therefore motivated to eliminate the singular behaviors by the inclusion of viscosity in the mathematical formulation such that the dissipative wave motion can be predicted.…”
mentioning
confidence: 99%
“…By a straightforward application of the Stokes method of stationary phase, the asymptotic representation of Eq. (21) can be given as…”
Section: Transient Waves Due To Instantaneous Line Disturbancesmentioning
confidence: 99%
“…6.4], [16,Sect. 3.7] and their generalized cases [1,4,5,[11][12][13][14][17][18][19][20][21][22][23]. It is found that the transient waves are dispersive.…”
Section: Introductionmentioning
confidence: 99%